Field report for Iowa bird life contributed by Erik Munson, spring 1984 - Munson, Eriket al (1984)
Field report for Iowa bird life was contributed by Erik Munson, spring 1984, with Bruce Roy Munson as another observer. Birds sightings include Water Pipits at Doolittle Prairie, Ruddy Turnstones and a Piping Plover at Hendrickson Marsh, a Green-backed Heron in eastern Story County, and, in Ames, a Great Blue Heron, a Chimney Swift, a Red-breasted Nuthatch, a Gray Catbird, and a Yellow-rumped Warbler. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1984. Epson - sheet feed/flatbed